Predator density modifies mosquito regulation in increasingly complex environments. Issue 6 (7th February 2020) - Buxton, Mmabaledi; Cuthbert, Ross N; Dalu, Tatenda; Nyamukondiwa, Casper; Wasserman, Ryan J
Abstract: BACKGROUND: Predation plays a pivotal role in the composition and functioning of ecosystems. Both habitat complexity and predator density are important contexts which may determine the strength of trophic and non‐trophic interactions. In aquatic systems, the efficacy of natural enemies in regulating vector pest species could be modified by such context dependencies. Here, we use a functional response (FR) approach to experimentally quantify conspecific multiple predator effects across a habitat complexity gradient of two notonectids, Anisops sardea and Enithares chinai, towards larvae of the vector mosquito Culex pipiens pipiens . RESULTS: E. chinai exhibited significantly greater consumption rates than A. sardea across habitat complexities, both as individuals and conspecific pairs. Each predator type displayed Type II FRs across experimental treatments, with synergistic multiple predator effects (i.e. prey risk enhancement) displayed in the absence of habitat complexity. Effects of increasing habitat complexity modified multiple predator effects differentially between species given behavioral differences, with habitat complexity causing significant antagonism (i.e. prey risk reduction) with multiple A. sardea compared to E. chinai. CONCLUSION: Habitat complexity effects on multiple predator interactions can manifest differently at the species level, suggesting emergent effects which complicate predictions of natural enemy impact in heterogenous environments. Considerations of density, diversity and habitat effects on efficacies of natural enemies should thus be considered by pest management practitioners to better explain biocontrol efficacies in increasingly diverse environments. © 2020 Society of Chemical Industry Abstract : Enithares exhibited greater mosquito consumption than Anisops as individuals and conspecific pairs. Habitat complexity caused more prey risk reduction with multiple Anisops compared to Enithares.